Putting Words to Work: Effects of Morphological Instruction on Children's Writing. (January 2014) - McCutchen, Deborah; Stull, Sara; Herrera, Becky Logan; Lotas, Sasha; Evans, Sarah
This quasi-experimental study examined effects of a 12-week, teacher-delivered, morphologically focused intervention on writing outcomes for fifth-grade U.S. students. In order to help students gain control over the morphologically complex words that typify academic writing, the intervention called students' attention to the morphological structure of words drawn from the district's science curriculum, taught morphologically related forms of those words, and provided opportunities for students to use morphologically related forms in reading and writing. Multilevel model results of posttests showed that, compared to control students ( n = 75), intervention students ( n = 95) included more morphologically complex words in a sentence-combining task, whether this was scored by a strict (correct spellings only) or lenient (plausible incorrect spellings accepted) criterion, and used more morphologically complex words that had been targeted in the intervention in their extended written responses. In addition, students with lower pretest scores on the sentence-combining measure showed greater intervention effects on the sentence-combining measure than did higher performing peers. Taken together, these results support the use of morphological instruction in the classroom, especially for students who struggle with writing.